CNS penetration of methotrexate and its metabolite 7-hydroxymethotrexate in mice bearing orthotopic Group 3 medulloblastoma tumors and model-based simulations for children. (February 2023) - Perkins, Rachel S.; Davis, Abigail; Campagne, Olivia; Owens, Thandranese S.; Stewart, Clinton F.
Abstract: The brain penetration of methotrexate (MTX) and its metabolite 7-hydroxymethotrexate (7OHMTX) was characterized in non-tumor bearing mice and mice bearing orthotopic Group 3 medulloblastoma. Plasma pharmacokinetic studies and cerebral and ventricular microdialysis studies were performed in animals dosed with 200 or 1000 mg/kg MTX by IV bolus. Plasma, brain/tumor extracellular fluid (ECF) and lateral ventricle cerebrospinal fluid (CSF) MTX and 7OHMTX concentration-time data were analyzed by validated LC-MS/MS methods and modeled using a population-based pharmacokinetic approach and a hybrid physiologically-based model structure for the brain compartments. Brain penetration was similar for MTX and 7OHMTX and was not significantly different between non-tumor and tumor bearing mice. Overall, mean (±SD) model-derived unbound plasma to ECF partition coefficient Kp, uu were 0.17 (0.09) and 0.17 (0.12) for MTX and 7OHMTX, respectively. Unbound plasma to CSF Kp, uu were 0.11 (0.06) and 0.18 (0.09) for MTX and 7OHMTX, respectively. The plasma and brain model were scaled to children using allometric principles and pediatric physiological parameters. Model-based simulations were adequately overlaid with digitized plasma and CSF lumbar data collected in children receiving different MTX systemic infusions. This model can be used to further explore and optimize methotrexate dosing regimens in children with brain tumors.